Animation Media to Improve Student Learning Results - Nadia Roosmalita Sari (Institut Agama Islam Negeri (IAIN) Tulungagung, 2018)
Learning methods in schools tend to use lecture and book models as learning media. Whereas at present, technology is growing rapidly. The use of technology as a learning medium is very important to attract students' interest in learning. At the Elementary School level, children still like learning while playing. This research proposes animation as a learning media for students in elementary schools. This media can be used by teachers as learning media. This animation media is expected to attract students' interest in learning, especially in mathematics subjects. In animation, visualization in the form of images moving on the subject of mathematics becomes one of the things that need to be optimized. The purpose of this study was to develop animation learning media as an alternative self-learning tool to help to master mathematics subjects for students and find out the feasibility of products for mathematics learning. The research and development methodology used in this study is Research and Development (R & D). This methodology covers all things related to development to produce quality interactive learning media software. Based on the trial, 81% of media experts, 88% of material experts, 70% of initial field tests, and 93% of field trials were obtained. Based on these results, the animation media for mathematics subjects has been feasible to be used as a medium of self-learning with an average value of 83% validation.